Evaluation of anterior cruciate ligament injury and intercondylar notch stenosis in patients with knee osteoarthritis with MRI - Ayşe Serap Akgün (Van Tıp Dergisi, 2020)
INTRODUCTION: We aimed to evaluate intercondylar notch morphology of femur in patients with knee osteoarthritis (OA) and to investigate the relation of anterior cruciate ligament (ACL) injury. Magnetic resonance imaging (MRI) was used to assess the femoral notch type, notch width index (NWI) and α angle in patients with OA or ACL injury and compare these differences. METHODS: The study was included 106 patients with OA and 79 healthy patients. Fifty-two of the patients with OA had ACL injuries (OA + ACL), 54 of them had no ACL injuries (OA-ACL). The intercondylar notch shape was classified as type A, type U or type W. NWI was the ratio of the width of the intercondylar notch to the width of the distal femoral condyles at the level of popliteal groove. The angle between the longitudinal femoral axis and the Blumensaat line was identified as the ‘α angle'. RESULTS: More type A notch and lower NWI values were seen in the OA + ACL group. No statistically difference was detected between the groups for α angle. When the regression analysis of the factors affecting the presence of ACL rupture was performed, it was shown that the strongest link was associated with the notch type and it was concluded that having type A notches increased the probability of rupture by 5.17 fold. DISCUSSION AND CONCLUSION: In osteoarthritic knees, there is a strong relationship between ACL injury and notch type and NWI; Type A notch type is the most powerful risc factor for ACL injury.